13-14-Year-Old (Adults) Children of The Quick Development of Methods and Tools for Power Quality - Eshberdiyev Olim Ruzimurotovich (Zien Journals, 2024)
This article is focused on improving qualities of fast-strength of those who engaged in sports-schools 13-14 - years-old basketball children, in the basketball training
Keywords: basketball; quick-power; sports school; physical qualities